Respuesta de la variedad de soya iniap 308 a dos distanciamientos de siembra, en la zona de Babahoyo- Provincia de Los Ríos” - Pazmiño Pérez, Jorge Eliecer (2013)
The present rehearsal was carried out in the properties of the Ability of Agricultural Sciences of the Technical University of Babahoyo, located in the Km 7 ½ of the road Babahoyo - Montalvo, with coordinated geographical 79º32'00" of longitude West and 01o 47'49" of South latitude and an altitude of 7,0 m.s.n.m whose general objective was to determine the answer of the soya variety 308 to two siembradistancings, in the City of Babahoyo - County of The Ríos, and the specific objectives: To evaluate agronomically of the variety INIAP 308, under the conditions of the area of Babahoyo; to identify the distance of more suitable siembra for this variety and in this area and to analyze the treatments economically. The national genetic material was used "INIAP 308", rushed by the National Institute of Agricultural Investigations (INIAP). The treatments were constituted by soya varieties INIAP 308 and P-34, and distancings of siembra of 0,40 and 0,60 m; using the design experimental Complete Blocks at random (DBCA) with four treatments and four repetitions. All the variables were subjected to the analysis of the variancia using the test of Multiple Ranges of Duncan. They were carried out all the practices and necessary agricultural works for the appropriate development of the cultivation like: preparation of the land, siembra, raleo, watering, control of overgrowths, fertilization, control fitosanitario and it harvests. The evaluated data were: days to the floración, days to the maturation, plant height, load height, vainas/plantas, granos/vainas, volcamiento, quality of the grain, weight of a hundred seeds (g), yield and economic analysis.